The late Pleistocene to Holocene palaeogeographic evolution of the Porto Conte area: Clues for a better understanding of human colonization of Sardinia and faunal dynamics during the last 30 ka. (22nd May 2017) - Palombo, M.R.; Antonioli, F.; Lo Presti, V.; Mannino, M.A.; Melis, R.T.; Orru, P.; Stocchi, P.; Talamo, S.; Quarta, G.; Calcagnile, L.; Deiana, G.; Altamura, S.
Abstract: The timing of the colonization of Sardinia by mammalian fauna and anatomically modern humans (AMH) is currently under debate. The understanding of the geological and palaeoclimatological conditions that characterized the Late Pleistocene and the Holocene is essential to investigate colonization processes and requires an integrated multidisciplinary approach. In this research we combine for the first time new radiometric dating, field evidence of relative sea-level changes (RSL), sea-level and glacial-isostatic adjustment modelling, stratigraphical, palaeontological, palaeoecological and isotope analyses that were performed on sites and finds from the Porto Conte and Capo Caccia area (Alghero, NW Sardinia). The most important Late Pleistocene fossiliferous deposits in Sardinia have been discovered in this part of the island. Modelled palaeogeographical reconstructions of the Porto Conte area combined with the inferred environmental context and chronology of Late Pleistocene faunal assemblages from Medusa-Dragonara Cave suggest that Homo sapiens did not inhabit this area before the Holocene. Our results support the hypothesis that human presence in Sardinia during the Last Glacial Maximum was at best sporadic.